Varieties of Untranslatability Exploring a potential system of classification for the discussion of untranslatability in literary texts - Gleeson, Liath (Graduate Students’ Union of the University of Dublin, Trinity College, 2015)
This paper outlines a new theoretical framework for the discussion of untranslatability in translation theory and practice. It reacts to the observation that the concept of untranslatability within Translation Studies has largely been treated as a homogenous idea, applicable without modification to any text. It builds upon the work of Emily Apter, Barbara Cassin, Susan Bassnett, David Bellos and others to show that the discussion of ‘untranslatables’ may in fact benefit from the recognition of multiple ‘untranslatabilities’ on various textual and non-textual levels. Five such strands of untranslatability are presented. The first encompasses sound patterns, syntax and linguistic humour, drawing from Bellos’ Is that a fish in your Ear? (2012) to argue for a specifically linguistic strand of untranslatability. The second highlights meaning transmission in the context of culture, examining the unique translation challenges posed by culturally-embedded texts like Cassin’s philosophical untranslatables and Stanisław Wyspiánski’s Wesele (1901). Strand three concerns what Walter Benjamin calls ‘the unfathomable’ element in translation, theorising that the loss of this mysterious element may result specifically from the many minor adjustments that inevitably occur during translation. Section four uses Carli Coetzee’s analysis of translation practice in South Africa to argue that social and cultural power relations can render a text untranslatable from the outside. The fifth section argues for the recognition of ‘absolute untranslatability’, drawing on Jean-Jacques Lecercle’s discussion of nonsense literature. Finally, the conclusion recognises both the malleability of the proposed framework and the dynamism of untranslatability as a concept in itself
Keywords: Theoretical Framework; Untranslatability; Translation Studies